236U Multi-modal Fission Paths on a Five-dimensional Deformation Surface*Supported by the Major Research plan of National Natural Science of China under Grant No. 11790324, the National Key Research and Development Program of China under Grant Nos. 2016YY0200804 and 2017YFF0206205, and the National Magnetic Confinement Fusion Science Program of China under Grant Nos. 2013GB106004 and 2012GB-101003 and the National Natural Science Foundation of China under No. 1179320013. (April 2019) - Wang 王, Zhi-Ming 智明; Zhu 朱, Wen-Jie 文杰; Zhu 朱, Xin 鑫; Zhong 钟, Chun-Lai 春来; Fan 樊, Tie-Shuan 铁栓
Abstract: In this paper, we develop a new path search algorithm which considers all the degrees of freedom and apply it on our calculated five-dimensional potential energy surface (PES) of 236 U. Asymmetric and symmetric fission paths and barriers are obtained .